Imagining Zoos - Rothfels, Nigel (Captures, 2022)
Beginning with paintings of dodos and cassowaries by the Flemish artist Roelandt Savery, this essay traces continuities between early-modern European menageries and 21st-century zoos. Arguing that modern zoos persist in attempting to present an imaginary world of superabundance, the article shows how today’s zoo simulations, mid-20th-century zoo-themed board games and toys, and a mid-19th-century paper zoo echo older attitudes toward “nature,” the “natural,” and the “exotic.”